Expeditious base-free solid-state reaction between phenyl boronates and hydrogen peroxide on silica gel. Issue 3 (4th January 2022) - Zhang, Li; Chen, Qianqian; Yang, Li; He, Yining; Guo, Keke; Yang, Jialin; Han, Ji-Min
Abstract : The expeditious base-free reaction between a phenyl boronate film and H2 O2 vapor can be realized on a silica gel surface, playing an important role in sensor manufacturing applications and chemical production. Abstract : The conversion of phenyl boronates to phenol with hydrogen peroxide (H2 O2 ) usually requires a base as a chemical assistant. In this work, we reported a base-free reaction between a phenyl boronate thin film and H2 O2 vapor on a nanostructured silica gel surface and the yield is determined as 80% in 25 s. A fluorescent compound C6NIB was used to monitor the reaction process in both solution and the solid state. The fluorescent tests suggested that the silica gel surface can effectively promote the phenyl boronate compound reacting with H2 O2 immediately on the solid state. Through control experiments, we determined the optimal reaction conditions. SEM, BET and water vapor adsorption characterization illustrated that the evenly distributed nanoscale pores and large surface areas of the silica gel interface may be critical for catalysis. Moreover, UV-vis absorption and reflection spectroscopy revealed that the final product of the base-free reaction was neutral phenol, instead of phenolate under basic conditions. Compared with traditional base-in reactions, the newly reported silica gel involved surface reaction could significantly extend the lifetime of the indicator molecules, resulting in excellent storage performance for practical sensing application. Finally, the simulation experiments identified the HO2 − /H3 O + ionic pair on the interacting Si–OH surface group pairs on the silica surface as the key for catalysis. Thus, the generated HO2 − then in turn reacted with phenyl boronate to form a phenol structure. The nanosized pores, arranged hydrogen bonding, and organized surface interface together led to this expeditious and effective base-free reaction between boronates and H2 O2 .